2019
DOI: 10.1016/j.ejon.2019.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of art therapy and coloring for professional and informal caregivers of patients in a radiation oncology unit: A mixed methods pilot study

Abstract: Caring for cancer patients can be highly stressful for both family caregivers and oncology professionals. These high levels of stress can lead to poorer patient outcomes and increased risk of health problems for the caregivers themselves. Art therapy may help these caregivers as art-making can be a relaxing and enjoyable form of self-expression and art therapists can support individuals in expressing and processing challenging emotions. Research on art-making or art therapy with caregivers of cancer patients h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 32 publications
2
36
0
1
Order By: Relevance
“…In the coloring condition, the relaxation and improved well-being likely came from the experience of distraction and completing a focused task. These findings align with those of Holt et al, 39 as well as Kaimal et al, 40 which suggested that coloring supports increased focus and mindfulness. Drake and Winner 41 identified distraction as a process of improved outcomes in individual visual expression.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the coloring condition, the relaxation and improved well-being likely came from the experience of distraction and completing a focused task. These findings align with those of Holt et al, 39 as well as Kaimal et al, 40 which suggested that coloring supports increased focus and mindfulness. Drake and Winner 41 identified distraction as a process of improved outcomes in individual visual expression.…”
Section: Discussionsupporting
confidence: 90%
“…Patients resolved initial feelings of anxiety as they engaged in open art through their session and established a sense of creative agency and self-efficacy. 20,40 With the support of an art therapist, patients can become familiarized with the different qualities of art materials and how to successfully achieve desired effects with art materials. Open studio may also assist patients in the exploration of existential and spiritual concerns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 2015 hits were retrieved. After deleting duplicates (N = 386), irrelevant papers (N = 580), and exclusions (N = 915), we found 17 studies eligible to be included in this scoping review as shown in Figure 1 (3,15,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Results Of the Database Searchmentioning
confidence: 99%
“…It has been reported that the use of art treatment therapies in the form of coloring, dedicated open art studio with therapeutic support within the oncological unit, psychodrama, and relaxation increase the oncologist in self-care and decreases anxiety, perceived stress, and burnout in both oncologist and family caregivers (15,40). Interestingly, participants with interest (or experience) in art-making were found to benefit more from this intervention (40). The motive behind the art-making intervention is to shift the attention of the stressed personnel away from their worries (40).…”
Section: Discussionmentioning
confidence: 99%